„Das is ja wohl eh klar.“: Eine Fallstudie zu Abtönungspartikeln und ihrer Verwendung in gesprochener Sprache - Stückler, Lena (Linguistik Online, 2023)
This article is dedicated to the particle subclass of modal particles and their supposed function of indicating the social proximity between speakers. This assumption stems mostly from the reference to shared knowledge of modal particles. This marking of the relations between the speakers occurs on the one hand through a high frequency of modal particles in conversational situations characterised by proximity, and on the other hand through the occurrence of certain modal particles. This paper deals with an empirical test of these assumptions. For this purpose, a corpus of twenty-two conversations in two different settings was used, one setting characterised by a close relationship and the other by unfamiliarity and social distance between the speakers. Within these conversations the frequencies of modal particles were collected and analysed in terms of their quantity and distribution. The results of the case study show that it is not all modal particles for which a function as relational markers can be assumed. Only the two particles ja and eh occur more frequently in the conversations characterised by social proximity. In addition to this, other factors like age and gender are highlighted that may influence the distribution of modal particles in this case study.